Dimensión conversacional de las cartas de Jorge Guillén a su hija, Teresa - Saiz-Cerreda, María del Pilar (2024)
The analysis of the letter as a conversation, though a standard approach of epistolary geography, nevertheless opens unsuspected horizons when considered from the perspective of the poetics of the genre. In the case of the letters of the Spanish poet Jorge Guillén to his daughter Teresa, the dialogic dimension of the letter configures the specific epistolary pact between the correspondents. Moreover, because of the variety of aspects in which this dimension manifests itself, it becomes the channel through which a narrative identity gradually develops. In this epistolary of monophonic structure, Jorge Guillén engages in a dialogue with his daughter, challenging her absence, to such an extent that her presence invades everything. The daughter's voice, which arrives as an echo and as a luminous reflection, irradiates and structures the father's epistolary writing and allows us to trace her personal ethos, which is configured throughout the epistolary.